Secondary embryogenesis and plant regeneration from leaf derived somatic embryos of Hevea brasiliensis - Kala R G; Jayasree P K; Jayasree R; Kuruvila P; Rekha K; Sobha S; Sushamakumari S; Thulaseedharan A (PLACROSYM XVIII. 10-13 December 2008, National Research Centre for Cashew, Puttur, Karnataka. Journal of Plantation Crops, 36 (3):218-222., 2008)
DL
Keywords: Hypocotyls; Leaf explants; Secondary embryogenesis; Somatic embryogenesis